2012
DOI: 10.1111/j.1365-2850.2011.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem among German nurses: does academic education make a difference?

Abstract: Self-esteem is not typically associated with the nursing profession. However, the concept is indispensible for job satisfaction and good-quality patient care. Many healthcare systems are confronted with declining numbers of qualified nurses, and desperately seek suitable strategies to recruit and retain sufficient trainees and junior staff. This investigation examined self-esteem in 212 German nurses using the Rosenberg Self-Esteem Scale. Nurses with an academic degree displayed a statistically significant hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
0
18
2
Order By: Relevance
“…The results of research conducted among 212 nurses in Germany using Rosenberg's Self-Esteem Scale indicated that nurses who had an academic degree displayed a statistically significantly higher level of self-esteem than nurses without an academic education. The type of professional training may therefore have a direct effect on self-esteem, thus offering a myriad of potential benefits to both nurses and patients [16]. Other studies have shown that the low self-esteem of nurses induces a service sabotage attitude, and that these nurses are less developed, both emotionally and chronologically, demonstrate less experience and have less education compared to their typical counterparts [17].…”
Section: Discussionmentioning
confidence: 99%
“…The results of research conducted among 212 nurses in Germany using Rosenberg's Self-Esteem Scale indicated that nurses who had an academic degree displayed a statistically significantly higher level of self-esteem than nurses without an academic education. The type of professional training may therefore have a direct effect on self-esteem, thus offering a myriad of potential benefits to both nurses and patients [16]. Other studies have shown that the low self-esteem of nurses induces a service sabotage attitude, and that these nurses are less developed, both emotionally and chronologically, demonstrate less experience and have less education compared to their typical counterparts [17].…”
Section: Discussionmentioning
confidence: 99%
“…Having a low education is associated with an increased risk of low self‐esteem , a major protective factor against poor mental health and strongly related to obesity . Likewise, living in a slum or otherwise deprived neighbourhood predicted poor self‐rated health, inflammation, obesity and the metabolic syndrome , as was living in a neighbourhood with high racial segregation .…”
Section: A Proposed New Model Of Obesity Causationmentioning
confidence: 96%
“…While the effects of organizational diversity have been examined widely in the management literature (Baum, Dutton, Karimi, & Kokkranikal, 2007;Martins & Parsons, 2007), there is an ambivalence in the literature about the impacts of diversity on work performance (Furunes & Mykletun, 2007;Pinar, McCuddy, Birkan, & Kozak, 2011;Testa, 2009;Zopiatis, Constanti, & Theocharous, 2014). Most research findings tend to indicate that diversity has the potential for positive effects (like increased creativity, innovation, and flexibility) as well as for negative effects (like worse communication, increased conflicts and stereotypes), and that the actual effects strongly depend upon context factors (see Pinar, et al, 2011;Rushton, 2007;Spataro, 2005;Tracey & Hinkin, 2008) or personal factors (see Chen & Choi, 2008;Derks, van Laar, & Ellemers, 2009;Furunes & Mykletun, 2007;Hogg & Terry, 2001;Lozano & Etxebarria, 2007;Sotelo, 2000;Van Eckert, Gaidys, & Martin, 2012).…”
Section: Introductionmentioning
confidence: 99%